Applications of the High Impact Practices in Family Planning during COVID-19. Issue 1 (1st January 2021) - Mickler, Alexandria K.; Carrasco, Maria A.; Raney, Laura; Sharma, Vinit; May, Ados V.; Greaney, Jennie
Abstract: The COVID-19 pandemic has substantially strained health systems across the globe. In particular, documented disruptions to voluntary family planning and reproductive health care due to competing health priorities, service disruptions, stockouts, and lockdowns are significantly impacting reproductive, maternal, newborn, and child health. As governments and family planning programmes grapple with how best to respond to the direct and indirect effects of the pandemic on family planning and reproductive health (FP/RH), the implementation and adaptation of evidence-based practices is crucial. In this commentary, we outline applications of the High Impact Practices in Family Planning (HIPs) towards COVID-19 response efforts. The HIPs are a set of evidence-based family planning practices which reflect global expert consensus on what works in family planning programming. Drawing upon preliminary COVID-19 data, documented experiences from prior health emergencies, and recommended programme adaptations from a variety of global health partners, we outline situations where specific HIPs may assist family planning programme managers in developing context-specific and evidence-based responses to COVID-19-related impacts on FP/RH, with the ultimate goal of ensuring the accessibility, availability, and continuity of voluntary family planning services across the world.